Crossover of Discrete Emotion and its Effect on Employees’ Wellbeing - Dayang Siti Aisah, Abang Suhaili; Zaiton, Hassan; Shahren, Ahmad Zaidi Adruce (UNIMAS Publisher, 2015)
The purpose of this study is threefold, that is, to examine discrete emotion and how it could contribute to the crossover phenomena in organizations, to examine how crossover affect employees’ burnout and engagement, to develop a theoretical framework of discrete emotion as mediator and its crossover in the relationship between job demand, resource and employees’ wellbeing. This paper examined past studies from Proquest, SAGE, Springer, JStor and Emerald online Database that are related to discrete emotion, spillover-crossover model, burnout and engagement. Fifty papers were reviewed from the online databases within the year 2004 to 2015. Findings show that discrete emotion has some effect on employees’ wellbeing through crossover phenomena process. Positive emotions, such as, joy and happiness can accelerate a person’s recovery from the physiological effects of negative emotions. Employees react to the antecedent and possess a discrete emotion. Employees’ discrete emotion makes crossover towards colleagues and triggers the intensity of their psychological state (engage, burnout). Practical intervention for human resource development professionals were suggested to assist employees and organizations on making it known about knowledge on discrete emotion and how it can affect employees’ wellbeing. This research produces a theoretical concept to examine the predictive potential of discrete emotion that leads to crossover phenomena in determining employees’ burnout and engagement.